Evaluation of a strain of Fuserium sp. for the management of the coffee berry borer, Hypothenemus hampei (Coleoptera: Scolytidae) - DÍAZ-P., PAULA ANDREA; GÓMEZ, YENNY ADRIANA; ZENNER DE POLANÍA, INGEBORG; VARGAS, AMPARO (Revista Colombiana de Entomología, 2003)
The coffee berry borer, Hypothenemus hampei (Ferrari), is the object of thorough studies to find an ambiently favorable management program. As a component of this 'program, native entomopathogenic fungi are of special importance. Recently, in Anolaima (Cundinamarca), a strain of Fusarium sp. was found to cause mortality of the adults of H. hampei. The objective of the present research is to evaluate the effect of a native strain of Fusarium sp. on the coffee berry borer under field conditions in order to perform preliminary characterization of the UDCAl strain. Another aim is to confirm the pathogenicity and to estímate the LD50 under laboratory conditions. The laboratory trials were conducted under controlled conditions of humidity (60%) and temperature (25± 2ºC). The field applications, with and without coadjuvant, were realized in a coffee plantation at l.550 m of elevation in a completely randomized design with three plots of 176 coffee trees each. Infestation percentage and the amount of fruit with Fusarium present, before and after the sprays, were evaluated. The results show that the mycelium of the entomopathogenic fungus has a whitish-pink color. Viewed under the microscope it is also septated, vacuolated, has abundant ovoid microconidia, scarce macroconidia and chlamydospores of diverse forms. The pathogenicity of the fungus was 62,5±9,57% with a mean time of 5,5±3,03 days. The LD50  found, presented 3X109 spores/ml. Under field conditions, after five applications, the percent mortality reached an increase of 33,3%. Precipitation had no detectable influence on the effect of the fungus. The use of a coadjuvant was only favorable under severe rainy conditions.